CONDITIONING OF SEEDLINGS OF PEPPERS (CAPSICUM ANNUM L.), INFLUENCED BY THE HYDROPONIC SYSTEM "FLOATING" - MELO, ANA RAQUEL PEREIRA DE; SOUSA, JOSÉ FLÁVIO FERREIRA DE; CONCEIÇÃO , CRISTIANE NUNES; OLIVEIRA, MARIA ROSELANE ALVES (IRRIGA, 2020)
CONDITIONING OF SEEDLINGS OF PEPPERS (CAPSICUM ANNUM L.), INFLUENCED BY THE HYDROPONIC SYSTEM "FLOATING" ANA RAQUEL PEREIRA DE MELO 1; JOSÉ FLÁVIO FERREIRA DE SOUSA2; CRISTIANE NUNES DA CONCEIÇÃO 3 E MARIA ROSELANE ALVES OLIVEIRA4 1 Engenheira Agrônoma, Instituto Federal do Maranhão - Campus Codó-MA, Rua do Poraquê S/N Codó Novo, Zona Rural, CEP: 65400000, Codó- MA, Brasil, anaraquel013@outlook.com; 2 Engenheiro Agrônomo, Instituto Federal do Maranhão - Campus Codó-MA, Rua do Poraquê S/N Codó Novo, Zona Rural, CEP: 65400000, Codó- MA, Brasil, jose.ferreira@ifma.edu.br; 3 Engenheira Agrônoma, Instituto Federal do Maranhão - Campus Codó-MA, Rua do Poraquê S/N Codó Novo, Zona Rural, CEP: 65400000, Codó- MA, Brasil, cristianenunes2996@gmail.com; 4 Engenheira Agrônoma, Instituto Federal do Maranhão - Campus Codó-MA, Rua do Poraquê S/N Codó Novo, Zona Rural, CEP: 65400000, Codó- MA, Brasil, roselany.alves@hotmail.com. 1 ABSTRACT The aim of this research to assess the development of pepper seedlings under different nutritional conditions, under the influence of the "Floating" aiming system, a new production, alternative for larger producers’ safety in producing sustainably, ensuring the production of healthy food and income generation. The production of seedlings occurred in polyethylene plastic trays, where they were placed 2/seeds paprika cells of Yolo Wonder cultivar. After the emergence of seedlings was thinning. The experimental design was completely randomized design, containing 5 treatments with 4 replications. The treatments were T1-trays remained out of the "floating", receiving water irrigation 2 times a day; T2-trays of floating, remained out more irrigation the same solution of the "floating" 3 times a week, using 500 ml of solution per Pan; T3-were pans 12:00 are in "floating" and 12:00 am out; T4-trays remained throughout the period of the test in the "floating"; T5-trays remained throughout the period in the "floating", except in the last week. The solution was composed of soluble fertilizer, calcium nitrate, potassium chloride, Triple Superphosphate and Urea, and was changed every Ten days. The parameters analyzed were height of the plant; Root length; Fresh matter weight of shoot; Weight of fresh root matter; Dry matter weight of shoot; Root dry matter weight; Diameter of the stem. All parameters analyzed were submitted to analysis of variance and averages compared by Tukey test to 1% in the case of significance. The treatment proved to be more feasible was the T4, as this medium to larger variables introduced height, stem diameter, plant fresh mass aerial and aerial dry mass. Keywords: Nutrient solution, production, safety, productive Alternative. MELO, A. R. P.; SOUSA, J. F. F.; CONCEIÇÃO, C. N. E OLIVEIRA, M. R. A. CONDICIONAMENTO DE MUDAS DE PIMENTÃO (CAPSICUM ANNUM L.), INFLUENCIADAS PELO SISTEMA HIDROPÔNICO “FLOATING” 2 RESUMO Objetivou-se com esta pesquisa avaliar o desenvolvimento de mudas de pimentão submetidas a diferentes condicionamentos nutricionais, sobre influência do sistema “Floating” visando, uma nova alternativa de produção, para propiciar aos produtores maior segurança em produzir sustentavelmente, para com isso garantir a produção de alimentos saudáveis e geração de renda. A produção de mudas ocorreu em bandejas de polietileno plástico, onde foram colocadas 2 sementes/célula de pimentão da cultivar Yolo Wonder. Após a emergência das plântulas, foi feito o desbaste. O delineamento experimental foi Inteiramente Casualizado, contendo 5 tratamentos com 4 repetições. Os tratamentos foram: T1- As bandejas permaneceram sempre fora do “floating”, recebendo irrigação de água 2 vezes ao dia; T2 – As bandejas permaneceram fora do floating, mais irrigação da mesma solução do “floating” 3 vezes por semana, usando 500 ml da solução por bandeja; T3 – As bandejas ficaram 24 h em “floating” e 24 h fora; T4 - As bandejas permaneceram todo o período do ensaio no "floating"; T5 - As bandejas permaneceram todo o período no "floating” ", exceto na última semana. A solução foi composta pelos fertilizantes solúveis, Nitrato de Cálcio, Cloreto de potássio, Superfosfato Triplo e Ureia, e foi trocada a cada Dez dias. Os parâmetros analisados foram: Altura da planta; Comprimento da raiz; Peso da matéria fresca da parte aérea; Peso da matéria fresca da raiz; Peso da matéria seca da parte aérea; Peso da matéria seca da raiz; Diâmetro do caule. Todos os parâmetros analisados foram submetidos à análise de variância e as médias comparadas pelo teste de Tukey a 1% no caso de significância. O tratamento que se mostrou mais viável foi o T4, pois este apresentou maiores médias para as variáveis altura da planta, diâmetro caulinar, massa fresca da parte aérea e massa seca da parte aérea. Palavras-chave: Solução Nutritiva, Alternativa de Produção, Segurança produtiva.